Pelatihan Pembuatan Poster menggunakan Canva sebagai Media Promosi LPK Zahra - Maryam, Maryam; Bagye, Wire (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
LPK (Job Training Institute) Zahra Computer is a course institution located at Jln Ahmad Yani Gerung No 10, Gerung Utara, West Lombok Regency, West Nusa Tenggara Province. LPK Zahra faced problems in promotion related to the poster design which was not attractive and took a long time. Therefore, training was conducted using Canva as a solution to improve staff skills in promotional poster design. Methods of implementing the training include preparation, implementation, and evaluation. The results of the training show an increase in knowledge and skills in using Canva to create attractive designs. The evaluation was carried out through a questionnaire using the Google Forms, and the results showed the participant’s satisfaction with the training. In conclusion, this training succeeded in increasing the participants' knowledge and skills in making posters using Canva as a promotional medium. Suggestions for the future are continuous training to maximize the application of the knowledge that has been obtained.